Konsep dan Praktik Metode Kualitatif untuk Penelitian Sosial - Nur Wulan Intan Palupi; Siti Risdatul Ummah; Pipit Larasati (RISOMA : Jurnal Riset Sosial Humaniora dan Pendidikan, 2025)
The complexity of social reality often cannot be fully captured through quantitative approaches. This article aims to elaborate on the fundamental concepts, types of strategies, and field practices involved in qualitative research, particularly within the realm of social sciences. Through a literature review employing a descriptive-critical approach, this paper provides a comprehensive discussion of the characteristics, objectives, and key stages of qualitative research, ranging from observation and interviews to documentation. Qualitative research emphasizes deep understanding of social and cultural contexts, as well as flexibility in responding to the dynamics of the field. Accordingly, this approach is highly relevant for researchers seeking to explore social phenomena in a more holistic and reflective manner. The findings of this study are expected to serve as a preliminary reference for both academics and practitioners in designing and conducting qualitative research effectively and responsibly.